Small world ebook A novel. - Zigman, Laura (2023)
"[A] brave and heartfelt book of truths."—New York Times Book Review (A Group Text Pick and Editors' Choice) A Boston.com Book Club Pick! From bestselling author Laura Zigman comes a heartfelt novel about two offbeat and newly divorced sisters who move in together as adults—and finally reckon with their childhood A year after her divorce, Joyce is settling into being single again. She likes her job archiving family photos and videos, and she's developed a secret comforting hobby: trolling the neighborhood social networking site, Small World, for posts that help solve life's easiest problems. When her older sister, Lydia, also divorced, calls to tell her she's moving back east from Los Angeles after almost thirty years away, Joyce invites Lydia to move into her Cambridge apartment. Temporarily. Just until she finds a place of her own. But their unlikely cohabitation—not helped by annoying new neighbors upstairs—turns out to be the post-divorce rebound relationship Joyce hadn't planned on. Instead of forging the bond she always dreamed of having with Lydia, their relationship frays. And they rarely discuss the loss of their sister, Eleanor, who was significantly disabled and died when she was only ten years old. When new revelations from their family's history come to light, will those secrets further split them apart, or course correct their connection for the future? Written with wry humor and keen sensitivity, Small World is a powerful novel of sisterhood and hope—a reminder that sometimes you have to look back in order to move ahead.